Bridging the Gap: Teachers' Empathy and Attitude toward Inclusion in Indonesian Kindergartens Setting - Khofidotur ROFIAH; Joanna KOSSEWSKA; Nur Ika Sari RAKHMAWATI (Communications of International Proceedings, 2023)
This study examines teachers' attitudes towards inclusion and their empathy on children with special needs in early childhood education settings in Indonesia. The research used Multidimensional Attitudes toward Inclusive Educational Scale (MATIES) consisting of three sub-dimensions: cognitive, affective, and behavioral and Empathy Quotient (EQ) to measure empathy levels. This study aimed to investigate the relationship between empathy and attitude among teachers in early childhood education. Furthermore, the study examined specific variables such as education level, inclusion training, and teaching experience concerning on teachers' attitudes towards including children with special needs in regular classrooms. A voluntary survey was given to 161 Indonesian teachers. The results showed a significant correlation between empathy levels and the three dimensions of teacher attitude towards inclusive education, encompassing cognitive, affective, and behavioral aspects among early childhood teachers in Indonesia.
Keywords: teachers' attitudes; empathy; Indonesian inclusive education